Lung/Polmone (C34.9) - Chemoradiation for stage III non-small cell lung cancer - Ramella, S.; Fiore, M.; Iurato, et al., A. (European Journal of Oncology and Environmental Health, 2013)
Summary. Approximately one third of patients with non-small cell lung cancer (NSCLC) have locally advanced  disease (stage III) and a few patients may benefit from surgical treatment exclusively. For this reason, the treatment of stage III NSCLC will require a combination of the three oncological disciplines: Cancer Surgery, Radiation Oncology and Clinical Oncology. The choice of treatment is guided by the presentation of the disease, indeed the patient is classified with locally advanced disease either for involvement of mediastinal structures (T3-T4) or for lymph node involvement showed at histological examination (pN2) or preoperative exams (cN2-N3). Therapeutic scenarios that we can observe are therefore an adjuvant treatment in patients who have an increased risk of local recurrence (pN2), a neoadjuvant treatment in patients with potentially resectable or borderline (cN2), and in patients with inoperable disease for bulky disease or contralateral lymph nodes (cN3) that need a radical treatment of radiochemotherapy. The multimodal approach is currently considered the best strategy but the timing needed to integrate the different disciplines and the use of various drugs in the combined treatment still has an incomplete classification. Recent studies and meta-analysis have tried to give an answer to these questions. Our aim is to present the latest data from the literature on different multimodal approach. La radiochemioterapia per il carcinoma polmonare non a piccole cellule stadio IIIRiassunto. Circa un terzo dei pazienti con carcinoma polmonare non a piccole cellule (NSCLC) ha una malattia localmente avanzata (stadio III) e pochi pazienti possono beneficiare di un trattamento chirugico esclusivo. Per questa ragione il trattamento del NSCLC stadio III prevede la combinazione delle tre discipline oncologiche: Chirugia Oncologica, Radioterapia Oncologica ed Oncologia Clinica. La scelta del trattamento è guidata anche dalla presentazione di malattia, infatti il paziente è classificato con malattia localmente avanzata o per coinvolgimento delle strutture mediastiniche (T3-T4) o per coinvolgimento linfonodale evidenziato all’esame istologico (pN2) o già presente agli esami preoperatori (cN2-N3). Gli scenari terapeutici che possiamo osservare sono quindi un trattamento adiuvante nei pazienti che presentano un aumentato rischio di recidiva locale (pN2), un trattamento neoadiuvante nei pazienti con malattia potenzialmente resecabile o borderline (cN2) ed infine i pazienti con malattia inoperabile o per malattia bulky o per linfonodi controlaterali (cN3) che necessitano di un trattamento radicale di radiochemioterapia. L’approccio multimodale attualmente è ritenuto la migliore strategia terapeutica ma ancora presenta una non completa classificazione sia nel timing con il quale devono integrarsi le diverse discipline sia nell’utilizzo dei farmaci da impiegare nel trattamento combinato. Recenti studi e meta-analisi hanno provato a dare una risposta a queste domande. Il nostro scopo è di presentare gli ultimi dati di letteratura sui differenti approcci multimodali.